2014
DOI: 10.1002/pds.3717
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin use and the risk for colorectal cancer

Abstract: Purpose Cardiac glycosides affect several pathways central for tumor formation. We sought to evaluate the association between digoxin use and colorectal cancer (CRC) risk. Methods We conducted a nested case-control study using The Health Improvement Network (THIN), a medical records database representative of the broader United Kingdom population. Study cases were defined as those with a diagnostic code for CRC. Each case was matched to up to 4 eligible controls on age, sex, practice site, and duration of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…We observed little evidence of increased colorectal cancerspecific mortality in digoxin users, providing some reassurance that digoxin is safe in colorectal cancer patients, despite recent evidence that digoxin users may have increased colorectal cancer risk (2). Our findings do not support a French study that observed reduced overall mortality with digoxin in 75 colorectal cancer patients (6), nor some preclinical studies suggesting that digoxin could have inhibitory effects on colorectal cancer cell growth (7).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We observed little evidence of increased colorectal cancerspecific mortality in digoxin users, providing some reassurance that digoxin is safe in colorectal cancer patients, despite recent evidence that digoxin users may have increased colorectal cancer risk (2). Our findings do not support a French study that observed reduced overall mortality with digoxin in 75 colorectal cancer patients (6), nor some preclinical studies suggesting that digoxin could have inhibitory effects on colorectal cancer cell growth (7).…”
Section: Discussioncontrasting
confidence: 56%
“…For instance, studies have shown increases in breast and uterus cancer probably related to estrogenic effects of digoxin (1). A recent large UK study reported a 40% increase in colorectal cancer risk in digoxin users (2), which the researchers suggest possibly reflects direct effects of the sodium potassium ATPase pump on tumorigenic pathways such as the Src/MAPK (3). In addition, preclinical studies have found that digoxin may reduce chemotherapy efficacy (4).…”
Section: Introductionmentioning
confidence: 99%
“…Antithrombotic treatment may also cause hematuria; however, only a small percentage of patients with macroscopic hematuria are diagnosed with prostate cancer 30. Second, other AF‐related treatments, such as amiodarone or digoxin, may also be associated with an increased risk of cancer,31, 32 and a causal relationship between AF per se and cancer may exist. However, both seem unlikely because of the strong association with metastatic cancer within 90 days, the initial sharp increase in the cumulative incidence of cancer, and the attenuation of the HRs over time, all of which suggest that cancer is already present at the time of the diagnosis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported correlations between HIF-1α expression and PDGF-B in breast cancer [36] and glioma [37]. In mice bearing triple negative breast cancer orthografts, lymphangiogenesis and lymphatic metastasis were shown to be blocked by treatment with the cardiac glycoside digoxin [38], which inhibits HIF-1α, or by the tyrosine kinase inhibitor imatinib via PDGFRβ targeting. This suggests that breast cancer patients might benefit from treatment aiming at targeting either HIF-1α or PDGFRβ alone or both together [36].…”
Section: Induction Of Rtk Ligandsmentioning
confidence: 99%